1982
DOI: 10.1139/v82-122
|View full text |Cite
|
Sign up to set email alerts
|

Abinitio SCF MO calculations on the reactions of OH radical with pyridine and pyridinium ion

Abstract: Relative energies of various products formed in the reaction of pyridine and pyridinium ion with the hydroxyl radical are calculated using non-empirical SCF MO techniques. The favourable electron delocalization in the meta-products, rather than the electrophilic character of the OH radical is the determining factor of relative stabilities. Calculated energy barriers along approximate reaction paths correlate with the available experimental information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…The observed results are in agreement with reported data giving no definite indication on the occurrence of HOC attack at the nitrogen site [27,28] and with reported SCF MO calculations indicating that delocalization of the odd electron in the hydroxylpyridine adducts favors their generation rather than hydroxyl addition to the N atom. [29] Contrary to our observations, Dey et al [28] suggested that an electron transfer was the preferred channel for the reaction of 3-aminopyridine with sulphate radicals. The one-electron oxidation potential of pyridine derivatives diminishes considerably with increasing electron donor ability of the substituents.…”
Section: Discussioncontrasting
confidence: 99%
“…The observed results are in agreement with reported data giving no definite indication on the occurrence of HOC attack at the nitrogen site [27,28] and with reported SCF MO calculations indicating that delocalization of the odd electron in the hydroxylpyridine adducts favors their generation rather than hydroxyl addition to the N atom. [29] Contrary to our observations, Dey et al [28] suggested that an electron transfer was the preferred channel for the reaction of 3-aminopyridine with sulphate radicals. The one-electron oxidation potential of pyridine derivatives diminishes considerably with increasing electron donor ability of the substituents.…”
Section: Discussioncontrasting
confidence: 99%
“…Although more information exists regarding reactions of OH with thymine and uracil, the greater experimental controversy for site preference of OH addition to cytosine lent impetus to the choice of cytosine as a subject for these calculations. A recent paper (8) suggested that site selection of OH attack of cytosine is more discriminating than for the analogous reactions with thymine and uracil and that the major product, in opposition to expectations from the results of our previous studies on OH reactions with N heterocycles (1,2), was the species favored on account of electrophilic interactions rather than being the most electronically delocalized product. These factors contributed to the selection of cytosine as the subject for study.…”
Section: Introductionmentioning
confidence: 58%
“…adducts suggests that an extension of the basis set would not overturn our conclusions. The geometry optimization for the most important species has been canied out to a uniform level of accuracy, higher than that routinely enforced in ab initio studies (vide infra) Initial geometries for both cytosine and species 2-7 were obtained from X-ray diffraction data (21) with the local geometry of the OH addition site assumed to be tetrahedral (1,2,5,6). Initial geometries of species 9 and 10 were taken from modified optimized geometries of the analogous keto forms of the adducts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy of the hydroxyl radical was that used in our study of the pyridine reactions. 6 In order to obtain some qualitative information on the kinetic aspects of the addition, assumed (nonoptimized) reaction paths were considered. At the given computational level, such reaction paths provide upper bounds for activation energies.…”
Section: Methodsmentioning
confidence: 99%